Wearable Conformal Metasurfaces for Polarization Division Multiplexing. Issue 13 (4th May 2020) - Li, Jiaqi; Zhang, Lei; Zhang, Min; Su, Hong; Li, Irene Ling; Ruan, Shuangchen; Liang, Huawei
Abstract: In practice, there is a strong requirement for modulating the performance of existing bulk devices without changing their physical geometry. In this study, by attaching a flexible metasurface on a cylindrical lens, a wearable conformal metasurface for terahertz polarization division multiplexing is demonstrated, which could be used in wireless communications, detection, and imaging. The integrated metasurface/lens can achieve the control functions of spot focusing, generation of Bessel beams, and phase holograms, respectively, for crosspolarized waves and line focusing for copolarized waves. A total modulation efficiency of up to 87% is experimentally obtained. Notably, the metasurfaces can be attached on/removed from existing bulk devices multiple times, without reducing the performances of both metasurface and conventional devices. As the flexible samples are fabricated using the cost‐effective standard flexible printed circuit technique, a multilayer conformal metasurface can be easily obtained for an efficient control. Furthermore, the same bulk device can be integrated with different flexible metasurfaces for various controls. Thus, the proposed metasurface can provide a promising flexible platform for various integrated applications and contribute to the development of wearable functional devices. Abstract : By attaching a flexible terahertz metasurface on a nonplanar bulk device, a wearable conformal metasurface for polarization division multiplexing is demonstrated. The metasurface can be attached on/removed from the functional device multiple times, without reducing the performances of both metasurface and conventional devices, which provides a novel approach for wearable functional devices.